What is the next chapter in the organized food retail industry in Portugal up to 2030, and what are the strategic options that should be considered for strategy formulation? - food waste in the Portuguese food retail industry - Marquês, Ana Gouveia (2022)
This Work Project focuses on the analysis of the evolution of the organized food retailers in Portugal, up to 2030. In the group component, two critical uncertainties were identified -shoppers’ e-commerce usage and producers’ direct-to-consumer adoption–and used as axes to create four plausible future scenarios. From the respective implications, strategic recommendations were provided. In the individual component(page 131), the food waste problematic was further developed. Following the identification of the main practices already in place, additional practices were recommended for the Portuguese food retailers, hoping to achieve amore sustainable future, benefiting the companies, involving communities and future generations.